"ABDULLA QAHHOR'S SKILL OF USING INDIVIDUAL ARTICLES - Shakhzoda Akbarova daughter of Alisher (Web of Journals Publishing, 2024)
This article highlights the importance of using word-rich articles, as well as methods of utilizing them, illustrated through the works of Abdulla Qahhor.
Keywords: Article, articles used without changes, articles used with modifications, articles created in the form of an article, brevity, effectiveness.